2010
DOI: 10.1017/s0007114509993576
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean dietary pattern among Balearic Islands adolescents

Abstract: The aim of the present work was to assess the prevalence of the Mediterranean dietary pattern (MDP) in Balearic Islands adolescents, and sociodemographic and lifestyle factors that might determine adherence to the MDP. A cross-sectional nutritional survey was carried out in the Balearic Islands between 2007 and 2008. A random sample (n 1231) of the adolescent population (12-17 years old) was interviewed. Dietary questionnaires and a general questionnaire incorporating questions related to socio-economic status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
50
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 42 publications
15
50
3
Order By: Relevance
“…Children who follow a healthy diet are those who might also maintain high levels of physical activity (53) . Despite no significant association between physical activity and the dietary patterns being obtained in the present study, in a previous study we found that sedentary and low-active adolescents showed the lowest adherence to the Mediterranean dietary pattern (11) .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Children who follow a healthy diet are those who might also maintain high levels of physical activity (53) . Despite no significant association between physical activity and the dietary patterns being obtained in the present study, in a previous study we found that sedentary and low-active adolescents showed the lowest adherence to the Mediterranean dietary pattern (11) .…”
Section: Discussioncontrasting
confidence: 99%
“…However, a progressive shift to a non-Mediterranean pattern, even in countries bordering the Mediterranean Sea, has been observed (44) . Previous studies carried out in Spain confirmed that young generations (5)(6)(7)(8)(9)(10)(11) are further away from the Mediterranean dietary pattern. Lately, we found that the average adherence to the Mediterranean dietary pattern in our adolescent population was 58 % (11) .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, this dietary pattern has a protective effect on weight gain (13,14) and the development of type 2 diabetes (8,14,15) . Despite the health benefits of the MD, several studies have reported that dietary pattern in the Mediterranean areas has been changing and switching to a more Westernized diet (15)(16)(17)(18)(19)(20) . Increased prevalence of diet-related diseases such as overweight and obesity among children in Greece (19,21) , Spain (13,22) and Italy (23,24) support the findings of these studies.…”
mentioning
confidence: 99%